Hematological Disorders in Children : Pathogenesis and Treatment - Ishii, Eiichi (Springer Singapore : Imprint: Springer, 2017)
This book describes the pathogenesis and treatment of several representative hematological disorders in children, with a special focus on genetic and molecular aspects. Research on the pathogenesis of hematological disorders in children has made remarkable strides; especially molecular target therapy has shown outstanding effects in refractory and conventional therapies for childhood leukemia. The findings presented in this book will broaden readers' understanding and hopefully spark new discussions leading to the development of new therapies including cell therapy and molecular target therapy, allowing clinicians to use more effective and less toxic approaches in the future. Hematological Disorders in Children will appeal to a wide readership, from medical students and beginning investigators to experienced scholars in the field of pediatric hematology and oncology seeking to broaden their understanding and keep up with the latest developments. It will also be of interest to the parents of pediatric patients, and to co-medical staffs.
Keywords: Medicine.; Hematology.; Oncology.; Pediatrics.; elektronické knihy; electronic books